2005
DOI: 10.1002/sim.1842
|View full text |Cite
|
Sign up to set email alerts
|

Analysing child mortality in Nigeria with geoadditive discrete‐time survival models

Abstract: Child mortality reflects a country's level of socio-economic development and quality of life. In developing countries, mortality rates are not only influenced by socio-economic, demographic and health variables but they also vary considerably across regions and districts. In this paper, we analysed child mortality in Nigeria with flexible geoadditive discrete-time survival models. This class of models allows us to measure small-area district-specific spatial effects simultaneously with possibly non-linear or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 26 publications
6
55
0
Order By: Relevance
“…Because of the seeming bride price to be earned, female children are often most favoured and better nourished than their male counterparts, resulting in skewed social and health consequences for children (Fuse 2010;Klasen 1996). Mother's working status and household income level have also been examined and found to affect child survival in the developing world (Adebayo and Fahrmeir 2005;Kalipeni 1993) …”
Section: Conceptual Issues Of Child Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the seeming bride price to be earned, female children are often most favoured and better nourished than their male counterparts, resulting in skewed social and health consequences for children (Fuse 2010;Klasen 1996). Mother's working status and household income level have also been examined and found to affect child survival in the developing world (Adebayo and Fahrmeir 2005;Kalipeni 1993) …”
Section: Conceptual Issues Of Child Mortalitymentioning
confidence: 99%
“…Some authors have examined spatial inequality in childhood morbidity and mortality in West African countries. Analysing data from Nigeria, Adebayo and Fahrmeir (2005) and Adebayo et al (2004) found Culled from reports of the DHS. Rates are based on 5 years prior to the dates of surveys significant variations in infant and child mortality based on geographical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Though sanitation is found to have more pronounced impact than water, the results also show that access to municipal water reduces the risk of mortality. A Bayesian geoadditive survival model was introduced by Adebayo et al (2002) to analyze child mortality in Nigeria. The results show the existence of a district-specific geographical variation in the level of child mortality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While early age at first birth has health implications, it also has economic implications. In addition, one study obtained in Nigeria reported that younger mothers (teenagers) are less likely in comparison to older mothers to breastfeed their children after birth, which means that the age of the mother at birth of a child influences whether the child will receive colostrum or not, which might affect the nutritional status of children (Adebayo and Fahrmeir 2005). Moreover, previous studies which were obtained in some developing countries have shown that some African countries do not allow girls back to go back school after they give birth.…”
Section: Mother's Age At Birthmentioning
confidence: 99%